Case report: role of cardiac MRI in the diagnosis of myocarditis - E. A. Butorova; O. V. Stukalova (Евразийский Кардиологический Журнал)
Diagnosis  of myocarditis   remains  one of the  most difficult  clinical problems  in cardiology.  In connection  with the coronavirus  infection COVID-19 caused by the acute respiratory virus SARS-CoV-2,  non-invasive diagnosis of myocarditis  is an urgent task. The most  informative method for  diagnosing  myocarditis  is  magnetic  resonance  imaging  [1,2]. The arsenal of MRI includes  a number of pulse sequences that make it possible to identify and evaluate the process  of inflammation in its various phases. Various pulse sequences  (T2-weighted images  or T2-mapping, delayed contrast, T1-mapping) allow not only to diagnose the disease, but also to determine  the stages  of damage.  The ability of MRI to differentiate ischemic and non-ischemic  lesions [3] is used in emergency cardiology for various myocardial injuries.The peculiarity of this clinical case  is the use of MRI diagnostics  in a patient with a typical clinical picture of acute coronary syndrome  in the emergency department of cardiology. The data of the contrast MRI of the heart allowed the patient to make the correct diagnosis.